2021
DOI: 10.3389/fragi.2021.741843
|View full text |Cite
|
Sign up to set email alerts
|

Drug Screening Implicates Chondroitin Sulfate as a Potential Longevity Pill

Abstract: Discovering compounds that promote health during aging (“geroprotectors”) is key to the retardation of age-related pathologies and the prevention of chronic age-related diseases. In in-silico and model organisms’ lifespan screens, chondroitin sulfate has emerged as a geroprotective compound. Chondroitin sulfate is a glycosaminoglycan attached to extracellular matrix proteins and is naturally produced by our body. Oral supplementation of chondroitin sulfate shows a high tolerance in humans, preferable pharmacok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…The longer this adulthood growth phase is, the longer-lived is an individual C. elegans (Hulme et al, 2010). To test whether this correlation is associated with prolonged production of the pattern I collagens, we used transgenic animals expressing GFP driven by the collagen col-144 promoter, whose expression gradually declines during aging (Ewald, 2021; Statzer et al, 2021a), and split this isogenic population grown in the same environment into high expression and low expression of P col-144 ::GFP transgenic animals at day 5 of adulthood. Animals expressing higher levels of P col-144 ::GFP at day 5 of adulthood lived longer than their genetically identical siblings with lower levels of col- 144 -driven GFP expressed (Figure 3F, Supplementary Table7), demonstrating that prolonged pattern I collagen expression is associated with longevity.…”
Section: Resultsmentioning
confidence: 99%
“…The longer this adulthood growth phase is, the longer-lived is an individual C. elegans (Hulme et al, 2010). To test whether this correlation is associated with prolonged production of the pattern I collagens, we used transgenic animals expressing GFP driven by the collagen col-144 promoter, whose expression gradually declines during aging (Ewald, 2021; Statzer et al, 2021a), and split this isogenic population grown in the same environment into high expression and low expression of P col-144 ::GFP transgenic animals at day 5 of adulthood. Animals expressing higher levels of P col-144 ::GFP at day 5 of adulthood lived longer than their genetically identical siblings with lower levels of col- 144 -driven GFP expressed (Figure 3F, Supplementary Table7), demonstrating that prolonged pattern I collagen expression is associated with longevity.…”
Section: Resultsmentioning
confidence: 99%
“…CRP is known to modulate innate immune response, promote platelet activation, vascular remodeling, and angiogenesis ( 89 ). Recent studies showed that CS intake is associated with a reduction in CRP concentration in blood, indicating decrease in inflammation ( 90 92 ). These findings, along with the significantly lower CRP levels in Morquio A patients found in this study, open a new direction in this field to gain insights in the understanding of vascular endothelial glycocalyx dysregulation in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the use of polysaccharides in our formulation instead of animal-derived proteins should reduce the immunogenic reaction risk and cost of raw materials. [20][21][22] Researchers typically apply biomaterials to cornea defects and crosslink in situ to form a tissue-adherent gel. Chemical crosslinking strategies specifically involving Nhydroxysuccinimide reactions and strain-promoted azide-alkyne cycloaddition have shown great promise in cornea repair.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the use of polysaccharides in our formulation instead of animal‐derived proteins should reduce the immunogenic reaction risk and cost of raw materials. [ 20–22 ]…”
Section: Introductionmentioning
confidence: 99%